Pengaruh Kualitas Produk dan Citra Merek Terhadap Keputusan Pembelian Smartphone Xiaomi-4X - Irwan Septayuda (MBIA, 2017)
The public's need for speed of information and communication demands a sophisticated cellular phone product to be more efficient. Access the internet, chat, e-mail is one of the needs of the community that must be fulfilled. Mobile phones that have all the ability called smartphone. Product Xiaomi is a popular smartphone because of its sophistication with an affordable price. In this study the author discussed about how product quality and brand image could influence consumer decisions in choosing the brand smartphone Xiaomi-4X. The respondents in this study were Xiome-4X hand phone users who lived in the city of Palembang. In this study the authors used descriptive quantitative analysis techniques using tabulation, multiple linear regression analysis, correlation coefficient, and significance test. The results showed that there was a significant influence between product quality and brand image on the purchasing decision of Xiaomi-4X product in Palembang City.